(untitled) (Research, Society and Development, 2020)
Know the concept of old age formed by elderly people who attend social centers. Qualitative study, with 12 elderly people who attend social centers. The collection of information took place from August to November 2019 through a semi-structured interview script. The data were analyzed according to Bardin. After analysis, the following thematic categories emerged: Gratitude to God; Loneliness; Ache; Difficulties in carrying out work; Changes in appearance; Memory deficit and the need for social support networks. Elderly people who attend social centers in general are grateful for the time they have lived and recognize it as a gift from God, however, negative conceptions about this conception predominated.